2023
DOI: 10.1002/smll.202208108
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Photocatalytic Hydrogen Production of Semiconductor Nanocrystal‐Based Hydrogels

Abstract: Destabilization of a ligand‐stabilized semiconductor nanocrystal solution with an oxidizing agent can lead to a macroscopic highly porous self‐supporting nanocrystal network entitled hydrogel, with good accessibility to the surface. The previously reported charge carrier delocalization beyond a single nanocrystal building block in such gels can extend the charge carrier mobility and make a photocatalytic reaction more probable. The synthesis of ligand‐stabilized nanocrystals with specific physicochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…This new direct self-assembly of CdSe-NPL-stacks in aqueous media opens up multiple processes and methods, such as gelation, [16][17][18][19] photocatalysis, [21] sensing, [24] ink-jet printing [20] and photoelectrochemistry, [13] for future applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new direct self-assembly of CdSe-NPL-stacks in aqueous media opens up multiple processes and methods, such as gelation, [16][17][18][19] photocatalysis, [21] sensing, [24] ink-jet printing [20] and photoelectrochemistry, [13] for future applications.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present work focuses on a direct selfassembly of NPL-stacks in aqueous solution (without polymer encapsulation) to open up the possible applications and methods, such as various gelation methods, [16][17][18][19] inkjet printing, [20] photocatalysis, [21] photo-electrochemistry, [12,13,22] photodetection [23] and sensing, [24] light emitting diodes, [25] and many more. For this approach CdSe NPLs are first transferred to aqueous solution via ligand exchange to 11-mercaptoundecanoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Combining this capability with the high porosity and free reactive surface makes them highly efficient photocatalysts compared to pure NP. [169][170][171] Generally, to achieve the maximum efficiency in photooxidation or photoreduction, the right choice of the appropriate hole or electron scavenger, or cocatalyst is crucial. [208,209] Numerous works on pure NPs are known in the literature, [210][211][212] which can be the basis and inspiration to develop highly efficient photocatalysts based on semiconductor NP-based gel networks.…”
Section: Summary and Outlook Nonordered Assembliesmentioning
confidence: 99%
“…Here, it was shown that the hydrogels show a significantly higher efficiency in hydrogen evolution compared to the nongelated NPs too (Figure 9b). [ 170 ] In both examples, the higher efficiency of the gels compared to nongelated NPs can be explained by the gelation process itself as well as the high porosity of the gel structure. To transfer the NP into its gel structure, a ligand exchange with short‐chain ligands is carried out beforehand, which shortens the distance from the surrounding medium to the NP surface, thus enabling better charge carrier transfer.…”
Section: Nonordered Assembliesmentioning
confidence: 99%
See 1 more Smart Citation